Trajetórias de educadores construídas na educação de jovens e adultos: experiências e significados - Emmeline Salume Mati (2008)
This paper aims at reflecting on the educational formation of History teachers who belong to a project of Young and Adult Education, called EJA. It tries not only to understand what such experience represents to their initial teaching formation but also to evaluate the need stated in the specific literature for a specific formation towards work with EJA. It consists of qualitative research whose sources are interviews with History teachers and classroom reports collected in the so called classroom notebooks. Six individuals- three women and three men participated in this investigation; their classroom notebooks have been read and analyzed and then, all the participants were interviewed. From the above mentioned documental data, it was possible to understand better the process of becoming a History educator within the EJA context. If, on one hand, it can be said that such a process is meaningful and relevant to the professional life of the individuals researched, on the other hand, some conflicts and tensions throughout their formation were detected. This study reveals that the constraints found are related to both formal aspects belonging to the university environment and to some difficulties in understanding specific features which characterize young and adult teaching professionals.